Black Girls and School Discipline: The Role of Teacher's Race, Pubertal Development, and Discipline Philosophy on Discipline Decisions. (June 2022) - Blake, Jamilia J.; Jackson, Lyric; Ruffin, Naomi; Salter, Phia; Li, Haoran; Banks, Courtney; Williams, Kayce Solari
The purpose of this study was to examine whether school discipline sanctions issued to female students are attributed to their racial background and developmental status and if this relation differs by teacher's racial/ethnic background and discipline philosophy. Drawing from a sample of 515 practicing educators from the United States, the authors used an experimental design to examine if teacher's discipline decision-making differed by student's race, student's developmental status, and teacher's racial/ethnic background and discipline philosophy. Results suggest that teacher's racial/ethnic background and discipline philosophy were the most salient predictors of discipline severity. Implications for future research on school discipline and Black girls are discussed.